A New Strategy for Selective Area Growth of Highly Uniform InGaAs/InP Multiple Quantum Well Nanowire Arrays for Optoelectronic Device Applications. (2nd July 2021) - Zhang, Fanlu; Zhang, Xutao; Li, Ziyuan; Yi, Ruixuan; Li, Zhe; Wang, Naiyin; Xu, Xiaoxue; Azimi, Zahra; Li, Li; Lysevych, Mykhaylo; Gan, Xuetao; Lu, Yuerui; et al.
Abstract: III‐V semiconductor nanowires with quantum wells (QWs) are promising for ultra‐compact light sources and photodetectors from visible to infrared spectral region. However, most of the reported InGaAs/InP QW nanowires are based on the wurtzite phase and exhibit non‐uniform morphology due to the complex heterostructure growth, making it challenging to incorporate multiple‐QWs (MQW) for optoelectronic applications. Here, a new strategy for the growth of InGaAs/InP MQW nanowire arrays by selective area metalorganic vapor phase epitaxy is reported. It is revealed that 110 faceted InP nanowires with mixed zincblende and wurtzite phases can be achieved, forming a critical base for the subsequent growth of highly‐uniform, taper‐free, hexagonal‐shaped MQW nanowire arrays with excellent optical properties. Room‐temperature lasing at the wavelength of ≈1 µm under optical pumping is achieved with a low threshold. By incorporating dopants to form an n + ‐i‐n + structure, InGaAs/InP 40‐QW nanowire array photodetectors are demonstrated with the broadband response (400–1600 nm) and high responsivities of 2175 A W −1 at 980 nm outperforming those of conventional planar InGaAs photodetectors. The results show that the new growth strategy is highly feasible to achieve high‐quality InGaAs/InP MQW nanowires for the development of future optoelectronic devices and integrated photonic systems. Abstract : A new facet engineering strategy is proposed to achieve the epitaxial growth of highly uniform InGaAs/InP multiple quantum well nanowires. The nanowires exhibit low threshold optically pumped lasing at room temperature and are fabricated into broadband photodetectors with high responsivity and fast response time. Such a growth strategy can pave the way for a wide range of nanoscale optoelectronic applications.